Comparative Evaluation of Predictive Ability of Comprehensive Geriatric Assessment Components Including Frailty on Long-Term Mortality. Issue 3 (27th May 2021) - Varan, Hacer Dogan; Kizilarslanoglu, Muhammet Cemal; Dogrul, Rana Tuna; Arik, Gunes; Esme, Mert; Kara, Ozgur; Kilic, Mustafa Kemal; Halil, Meltem; Cankurtaran, Mustafa; Yavuz, Burcu Balam
ABSTRACT: Background : This study aims to compare the predictive value of all comprehensive geriatric assessment (CGA) parameters with the predictive value of frailty assessment (with Edmonton Frailty Scale (EFS) and Fried Frailty Index (FFI)) for long-term mortality, in older adults. Methods : A total of 967 patients were included, consecutively. At the first admission, age, gender, comorbidities, number of drugs, and laboratory values of the patients were recorded. Each patient underwent CGA which consisted of anthropometric measurements, functional, cognitive, mood, nutritional, gait, fall, sleep duration, and frailty assessment. Fifty-seven months after the first admission, CGA parameters were analyzed to determine their predictive abilities on long-term mortality due to all causes, comparatively. Results : The median age was 73 years (range 65–94 years). The median follow-up time was 39.9 months (range 0.5–57.3 months). Serum albumin level, FFI, EFS, instrumental activity of daily living (IADL) score, and walking time were the best predictors of mortality. There was no significant difference between these parameters in predicting mortality. Conclusion : FFI and EFS have similar predictive value for mortality. In busy clinical practice, a new index based on IADL, walking time, and serum albumin level may be an alternative of frailty assessment for predicting mortality.